Effect of hypercortisolism on bone mineral density and bone metabolism: A potential protective effect of adrenocorticotropic hormone in patients with Cushing's disease. Issue 1 (January 2018) - Guo, Weihong; Li, Fengao; Zhu, Chonggui; Wang, Baoping; Wang, Kunling; Dai, Chenlin; Jia, Hongwei; Wei, Hongyan; He, Qing; Cui, Jin; Yuan, Menghua; Tang, Shaofang; et al.
Objective: To investigate the effects of Cushing's disease (CD) and adrenal-dependent Cushing's syndrome (ACS) on bone mineral density (BMD) and bone metabolism. Methods: Data were retrospectively collected for 55 patients with hypercortisolism (CD, n = 34; ACS n = 21) from January 1997 to June 2014. BMD was examined in all patients, and bone turnover markers were tested in some patients. Healthy controls (n = 18) were also recruited. Results: The lumbar spine and femoral neck BMD were significantly lower in the ACS and CD groups than in the control group. Lumbar BMD was significantly lower in the ACS than CD group. The collagen breakdown product (CTX) concentrations were significantly higher while the osteocalcin and procollagen type I N-terminal propeptide (PINP) concentrations were significantly lower in the ACS and CD groups than in the control group. The PINP concentration was significantly lower while the CTX concentration was significantly higher in the ACS than CD group. In the CD group only, lumbar BMD and serum adrenocorticotropic hormone had a significant positive correlation. Conclusions: Bone turnover markers indicated suppressed osteoblast and enhanced osteoclast activities. PINP and CTX changes might indicate bone mass deterioration. Adrenocorticotropic hormone might be protective for lumbar BMD in patients with CD.